2013
DOI: 10.1007/s00428-012-1362-4
|View full text |Cite
|
Sign up to set email alerts
|

In human invasive breast ductal carcinoma, tumor stromal macrophages and tumor nest macrophages have distinct relationships with clinicopathological parameters and tumor angiogenesis

Abstract: Tumor-associated macrophages play a crucial role in breast cancer progression and tumor angiogenesis. However, evaluation of tumor-associated macrophages incorporating their histological locations is lacking. The aim of this study was to clarify whether macrophages in tumor stroma and macrophages in tumor cell nests have distinctive properties in relation to pertinent breast cancer clinicopathological parameters and tumor angiogenesis. In 94 human invasive breast ductal carcinomas, tumor-associated macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…While TAM density in primary breast cancer has been correlated with poor prognosis 2628 , a CSC-niche involving TAMs has not been demonstrated microscopically in patient tumor tissues. We undertook to verify direct contact between TAMs and CD90 hi CSCs in patient breast cancer tissue by immunofluorescence analyses with anti-CD90 and -CD68 (a cell-surface protein expressed largely by macrophages) antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…While TAM density in primary breast cancer has been correlated with poor prognosis 2628 , a CSC-niche involving TAMs has not been demonstrated microscopically in patient tumor tissues. We undertook to verify direct contact between TAMs and CD90 hi CSCs in patient breast cancer tissue by immunofluorescence analyses with anti-CD90 and -CD68 (a cell-surface protein expressed largely by macrophages) antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…2012), pro-survival signaling through the AKT/PIK3 pathway (Yunta and Lazo 2003), or are expressed by tumor cells and TAMs in a variety of human cancers (Maniecki et al . 2012; Shabo and Svanvik 2011;Ch’ng et al . 2013; Feng et al .…”
Section: Discussionmentioning
confidence: 99%
“…The density of CD68 + TAMs in the tumor stroma, but not in the tumor nest, was an independent prognostic factor for reduced survival of patients with breast cancer. 35 Another report 36 indicated that high CD68 + TAM counts in the tumor stroma, but not in the tumor nest, were associated with higher tumor grades and negative estrogen receptor status, whereas those in the tumor nest were significantly correlated with microvessel density. The authors suggested that tumor stromal macrophages and tumor nest macrophages residing in different microenvironments have distinct roles.…”
Section: Breast Cancermentioning
confidence: 99%
“…34 Stromal TAMs linked to poor prognosis more closely than were intratumoral TAMs. 35,36 Lung cancer…”
mentioning
confidence: 99%